2014
DOI: 10.1007/s40265-014-0328-z
|View full text |Cite
|
Sign up to set email alerts
|

Dextromethorphan/Quinidine: A Review of Its Use in Adults with Pseudobulbar Affect

Abstract: Fixed-dose dextromethorphan/quinidine capsules (Nuedexta(®)) utilize quinidine to inhibit the metabolism of dextromethorphan, enabling high plasma dextromethorphan concentrations to be reached without using a larger dose of the drug. The drug combination is the first treatment to be approved for pseudobulbar affect (PBA), a condition of contextually inappropriate/exaggerated emotional expression that often occurs in adults with neurological damage conditions, such as amyotrophic lateral sclerosis (ALS), multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…As DMQ is an approved drug with an excellent safety profile [22], baseline laboratory studies were limited to a complete blood count, standard chemistry panel, and an electrocardiogram. The occurrence of adverse events was documented at each study visit, as well as at a final follow-up telephone call.…”
Section: Methodsmentioning
confidence: 99%
“…As DMQ is an approved drug with an excellent safety profile [22], baseline laboratory studies were limited to a complete blood count, standard chemistry panel, and an electrocardiogram. The occurrence of adverse events was documented at each study visit, as well as at a final follow-up telephone call.…”
Section: Methodsmentioning
confidence: 99%
“…Using a 20/10-mg dose combination, a small 12-week noncomparative trial demonstrated measurable improvement in pseudobulbar symptoms after 30 days (as measured by the Center for Neurologic Study-Lability Scale). 21 Though individuals enrolled in this trial appeared to tolerate this dose, additional trials still need to be conducted to more clearly determine its long-term safety and efficacy. It is not approved for dementia with agitation, but a phase 2 trial suggests a benefit compared with placebo in reducing agitation and caregiver burden.…”
Section: Dextromethorphan and Quinidinementioning
confidence: 96%
“…Dextromethorphan is another NMDA receptor antagonist that has been combined with quinidine, a CYP2D6 inhibitor responsible for reducing and stabilizing the metabolism of dextromethorphan into a single drug preparation. This combination of dextromethorphan combined with quinidine (AVP923) is clinically available in the USA for treatment of pseudobulbar affect [77]. Due to the clinical availability of this agent, and earlier studies showing efficacy, a small Phase IIa study in PD to treat LID is ongoing (Table 1) [18,78].…”
Section: -Htmentioning
confidence: 99%